Construction of micro-nano structured Si/C anode armed with rGO hollow spheres for high-performance lithium-ion hybrid capacitors - Wang, Yutai; Wang, Qunyi; Zhou, Xiaoyan; Ji, Puguang; Wang, Gongkai; Zhang, Chengwei; Sun, Mengxiao; Kurbanov, Mirtemir S. (Journal of alloys and compounds, 2024)
Because of the unique ability to combine high energy density with high power density, lithium-ion hybrid capacitors (LICs) have generated significant interest. Among the various anodes being explored for LICs, silicon (Si) stands out as a particularly promising anode material due to its high theoretical capacity. Nevertheless, the formidable challenge lies in the rapid capacity fade resulting from substantial volume expansion. Herein, a simple and efficient spray drying technique was used to fabricate a Si@rGO@NC composite with micro-nano structure. In this composite, Si nanoparticles are encapsulated between reduced graphene oxides (rGO) hollow spheres and a layer of carbon is coated on the surface of both the Si and the micron-sized composite particles, forming a rigid and mechanically stable structure. The composite combines the high activity of nano-Si with the industrially easy handling of micron-scale particles. Moreover, the rGO hollow spheres not only enhance the electrical conductivity but also buffer the volume expansion of the electrode and provide channels for the rapid transport of electrolyte/ions. Thanks to its advantageous structural features, the constructed LICs with activated carbon as cathode can achieve a Max. energy/power density of 253.1 Wh kg−1/10,824.1 W kg−1 and maintain 84.3 % of its initial capacitance after 8000 cycles. The micro-nano structured design concept of Si-based materials developed in our work could offer new insights and directions for the future development of Si-based energy storage devices. [Display omitted] •Si@N-doped carbon composite armed with rGO hollow spheres is prepared (Si@rGO@NC).•The Si@rGO@NC electrode shows high-rate capability in Li-ion half-cells.•Si@rGO@NC//AC LICs exhibit superior energy/power density and long lifespan.